Rapid detection of fumonisin B1 using a colloidal gold immunoassay strip test in corn samples. (15th December 2015) - Ling, Sumei; Wang, Rongzhi; Gu, Xiaosong; Wen, Can; Chen, Lingling; Chen, Zhibin; Chen, Qing-Ai; Xiao, Shiwei; Yang, Yanling; Zhuang, Zhenhong; Wang, Shihua
Abstract: Fumonisin B1 (FB1 ) is the most common and highest toxic of fumonisins species, exists frequently in corn and corn-based foods, leading to several animal and human diseases. Furthermore, FB1 was reported that it was associated with the human esophageal cancer. In view of the harmful of FB1, it is urgent to develop a feasible and accuracy method for rapid detection of FB1 . In this study, a competitive immunoassay for FB1 detection was developed based on colloidal gold-antibody conjugate. The FB1 -keyhole limpet hemoeyanin (FB1 -KLH) conjugate was embedded in the test line, and goat anti-mouse IgG antibody embedded in the control line. The color density of the test line correlated with the concentration of FB1 in the range from 2.5 to 10 ng/mL, and the visual limit detection of test for FB1 was 2.5 ng/mL. The results indicated that the test strip is specific for FB1, and no cross-reactivity to other toxins. The quantitative detection for FB1 was simple, only needing one step without complicated assay performance and expensive equipment, and the total time of visual evaluation was less than 5 min. Hence, the developed colloidal gold-antibody assay can be used as a feasible method for FB1 rapid and quantitative detection in corn samples. Highlights: Colloidal gold-antibody assay for rapid detection of fumonisin B1 was developed. The linear range to detect fumonisin B1 was 2.5–10 ng/mL by the assay. The visual limit for the fumonisin B1 detection by the way was 2.5 ng/mL. Colloidal gold-antibody assay to detect fumonisin B1 is specifial, fast and cheap.